Stand for semi-natural modeling of asynchronous radio information transmission systems - Yuri R. Butkevich; Sergey S. Loginov; Raushan R. Yarullin (Физика волновых процессов и радиотехнические системы)
Background. The article is devoted to the mathematical description of the stand for semi-natural modeling of asynchronous radio information transmission systems. Currently, the development of new asynchronous radio information transmission systems involves many problems before commissioning. The need to develop a stand for semi-natural modeling of asynchronous radio information transmission systems is an urgent task, as it will ensure a reduction in development costs due to the timely identification and elimination of shortcomings of radio systems at the test stage. Aim. The purpose of the work is to develop a mathematical description of the query channel of the semi-natural modeling stand, which forms a signal-interference environment that takes into account the properties of radio wave propagation, as well as the effects of various types of interference. Methods. In this work, analytical methods were used to obtain the resulting general expressions. Results. A mathematical description of such processes as the in-system flow of request signals and intentional interference is shown, as well as structural schemes for the formation of these types of interference are proposed based on the results obtained. Conclusions. The obtained results can be used to build a stand for semi-natural modeling of asynchronous radio information transmission systems.